2002
DOI: 10.1353/sof.2002.0013
|View full text |Cite
|
Sign up to set email alerts
|

Work Units and Income Inequality: The Effect of Market Transition in Urban China

Abstract: Nee's market transition theory claims that redistributive power will decline and returns to human capital will increase as state socialist economies are transformed into market economies.However, many other scholars have discovered that either the influence of redistributive power persists or returns to human capital decline. In this paper, I analyze the effect of marketization on individuals= income inequality in urban China as mediated by work units, which are classified into three types: Low Profit State Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 39 publications
(15 reference statements)
0
60
0
Order By: Relevance
“…Further, consumption practices and housing situations have also changed greatly in urban China. As discussed in the past literature (Bian 2002;Wu 2002;Xie, Lai, and Wu 2009), the ownership of a work unit (danwei) was historically strongly associated with one's economic welfare, especially during the Mao era. Working in the state-owned sector was commonly labeled as having "iron rice bowels" (tie fanwan), symbolizing advantages in many aspects of life, such as housing.…”
Section: Post-reform Chinamentioning
confidence: 99%
“…Further, consumption practices and housing situations have also changed greatly in urban China. As discussed in the past literature (Bian 2002;Wu 2002;Xie, Lai, and Wu 2009), the ownership of a work unit (danwei) was historically strongly associated with one's economic welfare, especially during the Mao era. Working in the state-owned sector was commonly labeled as having "iron rice bowels" (tie fanwan), symbolizing advantages in many aspects of life, such as housing.…”
Section: Post-reform Chinamentioning
confidence: 99%
“…Thanks to such remarkable economic achievements, China has been ranked the fourth largest economy in the world since at least 2005. The progress and economic gains in China, nonetheless, are achieved at the expense of rapidly escalating economic and social divisions between urban and rural areas and among geographic regions, as has been intensely discussed in the literature (e.g., Yao, et al, 2004;Wu, 2002;Fan and Sun, 2008). Furthermore, we argue that the economic inequalities have brought about growing discrepancies in opportunities for citizens to realize their aspirations and to enhance their personal and public health and wellbeing.…”
Section: Historical Patternsmentioning
confidence: 99%
“…Capitalizing on the huge regional unevenness in economic development that resulted from the unequal progress of the economic reform in China, Xie and Hannum (1996) found that income returns to education are higher in slow-developing cities than in fast-developing cities, with the pace of economic development measuring that of the economic reform. Walder (1990) and Wu (2002) also reported that returns to education were lower for bonuses set by work units (danwei ) than for base salaries set by the government. Most importantly, overwhelming evidence from previous research has shown that political power continues to play a major role in determining economic income in a variety of social contexts, especially when ownership of enterprises is ambiguous and the governments' role is strong (Walder 2002;Walder and Zhao 2006).…”
Section: Market Transition and Housing Inequalitymentioning
confidence: 99%
“…While income returns to education have indeed increased in China over time, it remains unclear whether this trend should be interpreted as supporting Nee's market transition theory (Hauser and Xie 2005). Most notably, researchers have found overwhelming evidence of the persistence of political power in determining income (Bian and Logan 1996;Walder 1990Walder , 1995Walder , 2002Walder and Zhao 2006;Wu 2002;Zhou 2000).…”
mentioning
confidence: 99%